Population ageing and sub-central governments Long-term fiscal challenges - Colin, Céline (OECD Publishing, 2019)
The population in OECD countries is ageing rapidly, which will have significant macroeconomic impacts, including on public expenditure and tax revenues. This paper analyses the consequences of population ageing at the sub-central government (SCG) levels and introduces the 'SCG fiscal vulnerability to ageing' indicator. This indicator identifies the countries in which SCGs on average are "vulnerable" to the ageing of their population from a fiscal perspective (both from the expenditure and revenue side). The paper posits that the economic and fiscal consequences of an ageing population goes beyond the central-SCG boundaries. Therefore, in order to make fiscal frameworks "ageing-resilient", countries require a coherent fiscal strategy, which focuses on tax and spending reforms, with a whole-of-government approach that brings together central governments and SCGs
Keywords: Taxation